2016
DOI: 10.1016/j.fluid.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of H2O–CaCl2 and H2O–CaCl2–CO2 mixtures

Abstract: a b s t r a c tMonte Carlo simulations were performed to obtain the phase behavior of binary H 2 O-CaCl 2 and ternary H 2 O-CaCl 2 -CO 2 mixtures over a range of conditions. The solubility of CO 2 in brines plays a key role in determining the amount that can be trapped via geological carbon storage. Isobaric-isothermal and Gibbs ensemble Monte Carlo simulations with several fixed-point charge force field models were used for the calculations of liquid densities and vapor pressures for the binary, and compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, since the solution is relatively incompressible, this difference in pressure is not enough to explain the difference in density between the simulations and experiments. Past simulations also show lower density than experiments for a number of different CaCl 2 force fields in SPC/E water . At 298.15 K, the solution density for the Mamatkulov et al model calculated by Mouc̆ka et al agrees well with the results in this work, except for the highest concentration point which shows some slight deviations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, since the solution is relatively incompressible, this difference in pressure is not enough to explain the difference in density between the simulations and experiments. Past simulations also show lower density than experiments for a number of different CaCl 2 force fields in SPC/E water . At 298.15 K, the solution density for the Mamatkulov et al model calculated by Mouc̆ka et al agrees well with the results in this work, except for the highest concentration point which shows some slight deviations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of Monte Carlo simulation to predict gas solubility in brines, such as CO 2 (Creton et al, 2018;Jiang et al, 2017;Liu et al, 2013;Tsai et al, 2016;Vorholz et al, 2004), H 2 S (Fauve et al, 2017), SO 2 and other diatomic light gases (Creton et al, 2018). However, to the best of our knowledge, no molecular simulation study dealing with the solubility of hydrogen in electrolyte solutions has been published.…”
Section: Introductionmentioning
confidence: 99%
“…This model allows to obtain a good accuracy for prediction of vapor pressures, saturated liquid densities and vaporization enthalpies of pure H 2 S (Kristof and Liszi, 1997;Ungerer et al, 2004). For water, the SPC/E model (Berendsen et al, 1987) is used since prior studies showed good results in the prediction of aqueous electrolyte properties with this model (Ji et al, 2012;Tsai et al, 2016). For Na + and Clions, the OPLS model is used (Chandrasekhar et al, 1984).…”
Section: Force Fieldmentioning
confidence: 99%
“…Although the water+salt system has been widely investigated in molecular simulation, the simulation of gas solubility in aqueous electrolyte solutions remains scarce and challenging due to high complexity of molecular interactions involving ionic species. Prior studies on this topic mainly concern CO 2 solubility in NaCl or CaCl 2 solutions (Liu et al, 2013;Tsai et al, 2016;Vorholz et al, 2004). To the best of our knowledge, no study dealing with the H 2 S solubility in aqueous electrolyte solution by molecular simulation has been published in open literature.…”
Section: Introductionmentioning
confidence: 99%